2019
DOI: 10.21203/rs.2.18509/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness-based interventions for children and adolescents: A scoping review protocol

Abstract: Background and purpose: Although mindfulness-based interventions (MBIs) are becoming increasingly popular, the application of MBIs with children and adolescents is still in its infancy. Mapping the existing literature is necessary to help guide pediatric mindfulness interventions. Our purpose is to synthesize the evidence of reported MBIs for children and adolescents with and without physical, mental, and cognitive disorders. Accordingly, we aim to identify trends and gaps in the literature, so that we can pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It includes different breathing techniques, imagination, and a range of methods to relax the body and mind (Viglas, 2015). The main elements used during mindfulness exercises are mindful body, breathing techniques, mindful movement, mindful looking and listening, mindful eating, mindful emotions, mindful heart, which involves kind thoughts, generosity, and thankfulness (Perrier et al, 2020). All the elements are included in abundance of exercises which can be also used and adapted for children.…”
Section: Introductionmentioning
confidence: 99%
“…It includes different breathing techniques, imagination, and a range of methods to relax the body and mind (Viglas, 2015). The main elements used during mindfulness exercises are mindful body, breathing techniques, mindful movement, mindful looking and listening, mindful eating, mindful emotions, mindful heart, which involves kind thoughts, generosity, and thankfulness (Perrier et al, 2020). All the elements are included in abundance of exercises which can be also used and adapted for children.…”
Section: Introductionmentioning
confidence: 99%
“…When brief MBIs are introduced within clinical primary care settings, adolescents have been shown to not only have improved psychological function but as well improve in other cognitive areas such as improved attention and academic scoring, thereby paving the way for a successful future as an adult (Crowley et al, 2018;Perrier et al, 2020). While considering the busy pace of a PCP practice, researchers have found that even brief fifteen-minute guided mindful meditation sessions introduced within care settings have allowed the meditators to reduce the amount of negative or repetitive thinking patterns, key symptoms of an anxiety diagnosis (Edenfield & Saeed, 2012;Marusak et al, 2018).…”
Section: Incorporating Brief Mindfulness Interventions During Adolescent Primary Care Visitsmentioning
confidence: 99%